Effects of aerodynamic loading on thin substructure within transonic region of subsonic aircraft - Abdul Rahman, Umran (2018)
As early as 2 months into service of Malaysia Airlines A380, flight crew reported fluttering noise within the vicinity of the upper deck door at position 2. Upon further inspection, it was found that a thin metal with non-metal composite substructure covering a void area on top of the aircraft door damaged. The substructure, also known as coverplate was replaced, however, within short cycle duration, the same component failed again. Located at slightly aft of the wing to fuselage junction, these damages confined only at this position although the same substructures are in placed on all the doors. After subsequent replacement, the mounting area on the door skin was found to be cracked. Mechanical analysis was performed and found that the fatigue life of the aluminium 2024 skin was used up by a flutter phenomenon. Precious ground time involved in repairing these cracks which extended to the whole door replacement pushes for an immediate solution to be made available. Adding to that, the risk of an inflight failure which may leads to a rapid decompression is too great for this problem to be taken lightly. Safety, cost, passenger comfort and company image are among the factors leading to these extensive studies. Unlike any previously known defect on the aircraft, of which the root cause of the problem can be easily identified and addressed quickly, this particular issue however, baffled all parties including the manufacturer as it affected A380 fleet all over the world. Compressible CFD simulation was conducted in finding the cause of this flutter. Of all the coverplates, only at this particular position; during cruise, an awkward pressure gradient occurs along the longitudinal axis of the substructure. This triggers the lifting of the forward edge of the part while the ram airflow causing it to peel out further. Once the shape distorted and the pressure equalized; due to its flexibility, the cover returns to its original position. The cycle continues. 4 different coverplate designs with varying stiffness being introduced to elevate this issue, all failed, and some even aggravated the damages to the door skin. However, basing from this study, an aerodynamically optimized coverplate was produced and tested over a period of 1 year at this specific location; no further damage was found and it was embodied as a permanent fix to this issue. These findings managed to highlight that even for a subsonic aircraft, the occurrences of a transonic region within the fuselage is a prevalence that require some detail attentions during the design stage. This is an important consideration prior to the placement of any exterior parts such as these coverplates, antennas, drain masts or probes that may protruded into the airflow where shockwaves could have formed and caused unforeseen effects.